Twin epidemics: The surging rise of methamphetamine use in chronic opioid users - Ellis, Matthew S.; Kasper, Zachary A.; Cicero, Theodore J. (Drug and alcohol dependence, 2018)
•Co-occurring opioid and methamphetamine use have doubled from 2011 to 2017.•Methamphetamine serves as an easily accessible and affordable substitute to opioids.•Co-occurring use provides synergistic effects whereby one balances out the other. Background/aims: Recent supply-side efforts enacted to curb the opioid epidemic have had both positive (i.e., prescription opioid abuse is on the decline) and negative outcomes (i.e., shifts to other drugs). Given methamphetamine is notably increasing in use across the United States, we sought to understand whether use of methamphetamine has increased among opioid users and whether there is an association between these two epidemics. Methods: Patients (N = 13,521) entering drug treatment programs across the United States completed an anonymous survey of drug use patterns from 2011 to 2017. A subset of these patients (N = 300) was also interviewed to add context and expand on the structured survey. Results: Past month use of methamphetamine significantly increased among treatment-seeking opioid users (+82.6%, p < .001), from 18.8% in 2011 to 34.2% in 2017. The Western region had the greatest increase in past month methamphetamine use (+202.4%, p < 0.001) and the highest prevalence rate in 2017 (63.0%). Significant increases (p < .001) in methamphetamine use were seen among males (+81.8%), females (+97.8%), whites (+100.6%), urban residents (+123.0%) and rural residents (+93.7%). Conclusions: Our studies show that there has been a marked increase in the past month use of methamphetamine in individuals with a primary indication of opioid use disorder. Qualitative data indicated that methamphetamine served as an opioid substitute, provided a synergistic high, and balanced out the effects of opioids so one could function “normally”. Our data suggest that, at least to some extent, efforts limiting access to prescription opioids may be associated with an increase in the use of methamphetamine.